Exposure of stellate ganglion to infrared laser - Mamilov, S. A. (Biophysical Bulletin, 2009)
This work was dedicated to study of change of capillary blood flow from exposure of the stellate ganglion to the infrared laser irradiation. There were used a pulsed laser that emits at wavelength 0,87 μm (impulse power 10, 30, 60 W; frequency 150, 1500, 3000 Hz, time impulse 80-95 ns) and a continuous wave laser that emits at wavelength 0,83μm (power 25, 50, 100 mW). The signal was registered by a two-wave detector and a pulseoximeter-spectrophotometer of original design. It was explored, that exposure of the stellate ganglion to the laser irradiation decreased transmission light, which indicates increase of finger blood flow at almost healthy volunteers. Maximal effect was observed from exposure of impulse irradiation power 60 W and frequency 3000 Hz.